ANALISA KOMBINASI PRODUK YANG OPTIMAL DALAM UPAYA MENINGKATKAN PRODUKTIVITAS PERUSAHAAN (STUDY KASUS PADA PT. XYZ) - Indriastiningsih, Erna (JURNAL GAUNG INFORMATIKA, 2015)
In the increasingly global and increasingly fierce competition in the industrial world today, every company is required to be able to utilize resources as efficiently as possible to achieve the objectives as effectively as possible. In relation to efficiency and effectiveness, the company must be able to increase productivity. Similarly, PT. XYZ who wants to increase the productivity of his company by analyzing optimal product combinations. This study aims to find out: (1) the model of forecasting each type of optimal product combination in the Company of PT. XYZ in order to predict the number of salesin the future; (2) the right and efficient combination of products that must be produced on the Company using Linear Programming. (3) the extent to which PT. XYZ can accept increases and decreases in orders. This research method is finding problems, formulating problems, carrying out secondary data retrieval from the Company andliterature studies, analyzing, solving problems and drawing conclusions. Analysis of the optimal product combination that has been done to increase the optimal product contribution that has been made can increase the contribution of theinitial margin of Rp. 674,903,112 and in the final repairs to Rp. 757,286,404, - or an increase of Rp. 82,383,292, -. While the optimal product product combination obtainedfrom 2010 was 440714.2 units, and gray cloth RYP 2026 was 470404.8 units. Besides that productivity also experienced an increase in the existing system list of 1.16 and inthe optimal product combination to be 1, 179. Then productivity rose by 0.019 or by 1.9% with the presence of product combinations.